O103 The relationship between routine pre-operative clinicopathological factors and post-operative infective complications in patients undergoing elective potentially curative colon cancer resection. (22nd July 2022) - Cheong, CM; Golder, A; Horgan, P; Roxburgh, C; McMillan, D
Abstract: Introduction: Post-operative complications, in particular infective complications, following elective colon cancer resection remain common. The present cohort study was designed to determine the influence of routinely reported clinicopathological factors on post-operative infective complications in a large regional cohort undergoing potentially curative colon cancer. Methods: Patients who underwent elective potentially curative colon cancer resection between January 2011 and December 2014 were assessed for post-operative complications. Clinicopathological data were recorded in a prospectively maintained database. A multivariate binary logistic regression model was used to identify independent risk factors for infective complications. Results: A total of 1887 patients were included with 29% of patients developing post-operative infective complications (POI). Multivariate analysis showed that factors associated for both POI complications and surgical site infections (SSI) were higher body mass index (BMI) (POI OR 1.29, 95% CI 1.15–1.46, p<0.001 and SSI OR 1.4, 95% CI 1.23–1.60, p<0.001), diabetes (POI OR 1.45, 95% CI 1.06–1.99, p=0.022 and SSI OR 1.58, 95% 1.12–2.22, p=0.009) and open or laparoscopic converted to open surgical approach (POI OR 0.66, 95% CI 0.52–0.84, p=0.001 and SSI OR 0.70, 95% CI 0.53–0.93, p=0.012). While 30-day mortality was associated with older age, high ASA grade and pre-operative systematic inflammatory grade. Conclusion: Elevated BMI and diabetes were independently associated with infective complications and surgical site infections. Therefore, the BMI and diabetes status should be routinely determined in patients undergoing elective surgery for colon cancer. Take-home message: Body mass index and diabetes status should be actively determined prior to elective surgical intervention to allow for risk stratification and pre-operative optimisations.